Bank Bonus Pay as a Risk Sharing Contract - Matthias Efing; Harald Hau; Patrick Kampkötter; Jean-Charles Rochet (Center for Economic Studies and ifo Institute (CESifo), 2019)
We argue that risk sharing motivates the bank-wide structure of bonus pay. In the presence of financial frictions that make external financing costly, the optimal contract between shareholders and employees involves some degree of risk sharing whereby bonus pay partially absorbs earnings shocks. Using payroll data for 1:26 million employee-years in all functional divisions of Austrian, German, and Swiss banks, we uncover several empirical patterns in bonus pay that are difficult to rationalize with incentive theories of bonus pay - but support an important risk sharing motive. In particular, bonuses respond to performance shocks that are outside the control of employees because they originate in other bank divisions or even outside the bank.
Keywords: G20; G21; D22; 330; banker compensation; risk sharing; bonus pay; operating leverage